ANALISIS KEMAMPUAN MANAJEMEN WAKTU PESERTA DIDIK SD KELAS 6 - Sibarani, Herlin Aryani; Naibaho, Hottua Diningrat; ,M.Pd, Syahrial (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to analyze the time management skills of grade 6 elementary school students using a quantitative descriptive approach.  Students' time management abilities are categorized into three levels: low, medium, and high.  Data was obtained from 18 students through questionnaires and observations.  Data analysis was carried out using descriptive statistical techniques to identify the distribution of time management abilities.  The research results show that the majority of students are in the medium category, indicating that their time management skills are quite good for their age.  However, some students are still in the low category, while a small number are in the high category.  Effective time management skills are important to increase student efficiency, productivity, and discipline in academic and extracurricular activities.  These findings provide valuable insights for students, parents, and teachers in helping students better manage their time, preparing them for future challenges.  This study also highlights the importance of developing time management skills from an early age to build a strong foundation for students' future development.  It is hoped that the results of this research can make a positive contribution in increasing awareness of time management among elementary school students and motivate efforts to develop this ability in the educational environment.